Estrategias Metodológicas para el desarrollo de la comunicación asertiva en los estudiantes de bachillerato - Ramírez Lema, Romina Estefanía (2024)
The main objective of this research study entitled "Estrategias metodológicas para el desarrollo de la comunicación asertiva en los estudiantes de bachillerato" was to determine the importance of methodological strategies for the development of assertive communication in high school students. The research work was carried out using a quantitative approach and a non-experimental design. In addition, field research was used. For the collection of information, a survey was applied as a technique, whose instrument had 23 items applied to 9 high school students of the Educational Unit "Leonardo Da Vinci". The data analysis allowed us to know the range of assertiveness of the students both as a course, as well as individually by several students according to the Assertiveness Scale proposed by Shelton and Burton (2004) in their book "Assertiveness. Make your voice heard without shouting". As a result of the study, it was determined that there is a high percentage of assertiveness in terms of the course, which allows for adequate assertive communication. In the same way, there are some students with whom this social skill needs to be developed. Three strategies were proposed as the problem method, role play, and the case method that can be worked in class to improve the assertive communication of students with the help of the tutor, as the three methodological strategies promote collaborative work, as well as the development of the trilogy of knowledge of students, knowing how to know, knowing how to do and knowing how to be.